GLOCALIZATION OF TRADITIONAL CULINARY (STUDY ON MOTHERS AS CULINARY SOCIALIZATION AGENT IN EARLY CHILDHOOD, SUB-DISTRICT MEDAN BARAT, MEDAN CITY) - Wisnu Rahdiansyah; M Nazaruddin; Saifuddin Yunus (Malikussaleh Social and Political Reviews, 2022)
Glocalization (Study Of Mothers As Socialization Agents In Introducing Contemporary Traditional Local Cuisine To Early Childhood), this research was conducted in the district of Medan Barat, Medan City. The first focus: in this study, why at an early age children tend to like fast food (Junk Food) compared to local cuisine with contemporary traditional flavors. Then, Second: knowing what drives mothers as agents of socialization in introducing contemporary traditional local culinary delights to early childhood. Third: knowing how the strategy is carried out by a mother and the local government in maintaining contemporary traditional local culinary in early childhood in the current era of globalization. This study uses a qualitative method with descriptive analysis, the data is analyzed through data reduction, data presentation and drawing conclusions. The theory used in this study is the theory of socialization according to Peter L. Beger which consists of mothers as agents who give birth to glocalization of traditional local culinary. The results of the study show that there are changes experienced in early childhood in generalizing traditional local cuisine among the community. In the first finding: Fast food cuisine was chosen because of the fast and unique way of serving it in its packaging to be enjoyed by these young children, as well as having a fairly expensive price to enjoy fast food once. Second: Knowledge of parents, especially a housewife or mother who has a career outside the home is also influenced by the level of education possessed by each individual, this is what makes mothers socialize to their children to keep eating nutritious foods such as traditional local culinary. And Third: The government's role has not been considered effective when viewed from the three aspects, namely: Regulator, Dynamist, and Facilitator.